Population genetic structure and demographic analysis of Eleutheronema rhadinum (Jordan and Everman 1902) and Eleutheronema tetradactylum (Shaw 1804) - Wahid, Nurul Atikah; Esa, Yuzine; Mohamed, Rozihan; Ismail, Muhammad Fadhil Syukri (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
The East Asian fourfinger threadfin, Eleutheronema rhadinum and four finger threadfin, E. tetradactylum (Shaw, 1804) were two species of the Polynemidae family that can be found in Malaysian waters. There no population genetic studies in both species in Malaysia, which were important to provide genetic information for sustainable fisheries management of the two species. Both species were also difficult to distinguish morphologically, thus their taxonomic classification were not fully resolved. Therefore, thus study aims to determine the levels of genetic divergences between the two Senangin fishes, and to quantify their population genetic structure and demographic patterns using mitochondrial DNA. Totally 151 samples were collected from 6 locations around Malaysian coastal water. Samples were obtained from commercial fishing activities. Muscle tissue were taken and stored in a 95% ethanol. Total DNA was extracted. The amplification of mitochondrial DNA (mtDNA) cytochrome c oxidase I (COI) gene (~630 bp) was obtained. All results were statistically analyzed to determine the genetic variations at the intra and inter-specific levels, and demographic patterns for both species. Among 151 individuals, 20 distinct haplotypes were defined. The phylogenetic (maximum likelihood tree) showed two genealogical branches were recognized among the haplotype, this also proven in pairwise distance among the haplotypes. Level of genetic divergence was substantially high (15-17%) supported their taxonomic status as distinct species. The nucleotide diversity was low in E. rhadinum and E. tetradactylum. Both species show the sharing of haplotypes between different populations and this provided support that both species had a historically widespread natural distribution in the region in the past. The levels of genetic differentiation, population structure and demographic patterns between the two species were successfully quantified.